2016
DOI: 10.1111/cge.12854
|View full text |Cite
|
Sign up to set email alerts
|

De novo loss of function mutations in KIAA2022 are associated with epilepsy and neurodevelopmental delay in females

Abstract: Intellectual disability (ID) affects about 3% of the population and has a male gender bias. Of at least 700 genes currently linked to ID, more than 100 have been identified on the X chromosome, including KIAA2022. KIAA2022 is located on Xq13.3 and is expressed in the developing brain. The protein product of KIAA2022, X‐linked Intellectual Disability Protein Related to Neurite Extension (XPN), is developmentally regulated and is involved in neuronal migration and cell adhesion. The clinical manifestations of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 23 publications
1
30
0
1
Order By: Relevance
“…These genes could be considered critical in the evaluation of individuals with epilepsy and NDD. Of note, the rate of gene discovery for genetic epilepsies has been significant in recent years and additional potentially high‐yield genes have been reported recently (ie, DEPDC5, KCNT1, IQSEC2, KIAA2022 , and SLC6A1 ) . Based on our results and limited published evidence, the CACNB4, EFHC1, SRPX2 , and ATP6AP2 genes appear to be low‐yield and variants in these genes should be reviewed cautiously.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…These genes could be considered critical in the evaluation of individuals with epilepsy and NDD. Of note, the rate of gene discovery for genetic epilepsies has been significant in recent years and additional potentially high‐yield genes have been reported recently (ie, DEPDC5, KCNT1, IQSEC2, KIAA2022 , and SLC6A1 ) . Based on our results and limited published evidence, the CACNB4, EFHC1, SRPX2 , and ATP6AP2 genes appear to be low‐yield and variants in these genes should be reviewed cautiously.…”
Section: Discussionmentioning
confidence: 58%
“…Of note, the rate of gene discovery for genetic epilepsies has been significant in recent years and additional potentially high-yield genes have been reported recently (ie, DEPDC5, KCNT1, IQSEC2, KIAA2022, and SLC6A1). [29][30][31] Based on our results and limited published evidence, the CACNB4, EFHC1, SRPX2, and ATP6AP2 genes appear to be lowyield and variants in these genes should be reviewed cautiously. When variants are identified in a proband, parental testing should be considered to clarify the clinical significance of the variant and determine recurrence risk for the family.…”
Section: Discussionmentioning
confidence: 83%
“…The pathogenic variant found in Patient 1, c.652C > T(p.Arg218*), was previously reported in a female patient described by de Lange et al () and Webster et al (). When comparing our patient to the female patient, the two share some of the same features including hypotonia, a broad‐based gait, and postnatal growth retardation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Charzewska et al () reported a family with two patients with whole gene duplication spanning a 384‐kb segment, but interestingly with decreased expression of KIAA2022 protein in fibroblasts and lymphocytes. A recent paper described five females with de novo pathogenic variants in KIAA2022 , most of them described as nondysmorphic and with mild to severe intellectual disability (Webster et al, ). Skewed X‐inactivation in the brain was presented as the possible explanation for the differences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation